2013
DOI: 10.1007/978-3-642-38233-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Barrier Coverage with Relocatable Sensors in the Plane

Abstract: We consider several variations of the problems of covering a set of barriers (modeled as line segments) using sensors that can detect any intruder crossing any of the barriers. Sensors are initially located in the plane and they can relocate to the barriers. We assume that each sensor can detect any intruder in a circular area of fixed range centered at the sensor. Given a set of barriers and a set of sensors located in the plane, we study three problems: (i) the feasibility of barrier coverage, (ii) the probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…for reasons of surveillance. Such studies usually wish to minimize the number of sensors used or the total energy required [17,25,33,42,48].…”
Section: Introductionmentioning
confidence: 99%
“…for reasons of surveillance. Such studies usually wish to minimize the number of sensors used or the total energy required [17,25,33,42,48].…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed polynomial-time algorithms for several special cases of the problems, e.g., barriers are parallel or perpendicular to each other, and sensors have some constrained movements. In fact, if sensors have different ranges, by an easy reduction from the Partition Problem as in [9], we can show that our problem MBC is NP-hard even for the line-constrained version and m = 2.…”
Section: Related Workmentioning
confidence: 93%
“…Dobrev et al [9] studies several problems on covering multiple barriers in the plane. They showed that these problems are generally NP-hard when sensors have different ranges.…”
Section: Related Workmentioning
confidence: 99%
“…In [10], the complexity of the MinMax and MinSum problems when sensors are initially placed in the plane and are required to relocate to cover parallel or perpendicular barriers is studied. The authors show that while MinMax and MinSum can be solved using dynamic programming in polynomial time if sensors are required to move to the closest point on the barrier, even the feasibility of covering two perpendicular barriers is NP-hard to determine.…”
Section: Related Workmentioning
confidence: 99%